Assessment of Public Services Quality in Libya (International Journal of Scientific Research and Management (IJSRM), 2021)
One of the main dimensions of good governance, which was adopted by the World Bank, is to ensure government provides quality services to its citizens. This dimension is very essential for the implementation of government policies and programs. For this reason, the government has to be accountable to all of their people about their services if their quality is not good. This study adopted quantitative method for primary data collection through questionnaire survey. The results from the data which was gathered from the Libyan people revealed that the Libyan people disagree with the rule of law as it does not enhance provision of good quality services, and they have no trust for the current laws by the government because they are not accountable. The reasons for their views were due to the fact that most of the laws are not just laws. The study recommended that there is need to ensure the independence of the legislative institution via the constitution of the state, and also ensure the independence of the judiciary in order to enhance the ability of the institution to work freely without pressure from the government.